A Metode Pembelajaran Menurut Al-Qur’an - Muh. Dahlan Thalib (IAIN PAREPARE, 2021)
Al-Qur'an in exerting its education on human beings confronts and treats these creatures in accordance with the elements of their creation, namely body, mind, and soul. Therefore, the educational materials presented in the Al-Qur'an always refer to the human soul, mind, and body. Educational and learning methods that can be used as hudan in the Qur'an can be identified in deductive, inductive, discussion, question and answer methods, story or storytelling methods, discovery and inquiry, survey toladan, and problem solving. Al-Quran is true that there are still many and there are areas where the reach of human knowledge is limited, such as matters of the spirit, the Day of Judgment, and so on.